EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW YANG BERORIENTASI PADA PENEMUAN TERBIMBING DENGAN PENGGUNAAN ALAT PERAGA PADA MATERI BANGUN DATAR SEGI EMPAT DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIKA - Djumaliningsih, Nosa Putri; Riyadi, Riyadi; Iswahyudi, Gatut (Journal of Mathematics and Mathematics Education, 2012)
ABSTRACTÂ This research aims to find out: (1) which one providing better mathematics learning achievement, the learning using guided inquiry-oriented Jigsaw type of cooperative learning model, Jigsaw type of cooperative or conventional learning model in rectangular flat structure material, (2) which one having mathematics learning achievement, the student with high, medium, or low mathematics reasoning skill in rectangular flat structure material, (3) in each mathematics reasoning skill (high, medium, and low), which one providing better learning achievement between guided inquiry-oriented Jigsaw type of cooperative learning model with visual aid use, Jigsaw type of cooperative or conventional learning model in rectangular flat structure material, (4) in each learning model (guided inquiry-oriented Jigsaw type of cooperative learning model with visual aid use, Jigsaw type of cooperative or conventional), which one providing better mathematics learning achievement, the students with high, medium or low mathematics reasoning skill in rectangular flat structure material.This study belonged to a quasi-experimental research with a 3x3 factorial design taken place in VII grade of SMPN Ponorogo in second semester of 2011/2012 school year. The population of research was all VII graders of Junior High Schools in Ponorogo, consisting of 51 school. The sampling technique used was stratified cluster random sampling. The classification of school was made according to National Examination value in the school year of 2010/2011. The samples of research were 280 students from SMPN 2 Ponorogo for high classification, SMPN 6 Ponorogo for medium classification, SMPN 2 Babadan for low classification. The data of mathematic reasoning skill and learning achievement were collected using a multiple-choice test. Technique of analyzing data used was a two-way variance analysis with different cells.The conclusions of research were (1) there was an effect of learning model on the learning achievement (Fobs = 8.10 > FÂtable = 3), from inter-row mean comparative test, it could be found that the guided inquiry-oriented Jigsaw type of cooperative learning model with visual aid use (marginal mean of 74.0833) provided better achievement than Jigsaw type of cooperative did (marginal mean of 69.5652) and both of them provided better achievement than the conventional learning model did (marginal mean of 65); (2) there was an effect of student mathematics reasoning skill on the learning achievement (Fobs = 32.74 > FÂtable = 3), from inter-row mean comparative test, it could be found that the students with high reasoning skill (marginal mean of 74.8785) provided reasoning skill equaling to the students with medium reasoning skill did (marginal mean of 71.5506), and both of them provided better achievement than the students with low reasoning skill did (marginal mean of 60.8571); (3) in high reasoning skill, the guided inquiry-oriented Jigsaw type of cooperative learning model with visual aid use provided achievement equaling to the Jigsaw type of cooperative did and both of them provided achievement equaling to the conventional learning model did, while in medium and low reasoning skill, the three learning model provided the same learning achievement; (4) in the guided inquiry-oriented Jigsaw type of cooperative learning model with visual aid use, the students with high mathematics reasoning skill had mathematics learning achievement as same as those with medium mathematics reasoning skill had, and both of them had mathematics learning achievement as same as those with low mathematics reasoning skill had, while in Jigsaw type of cooperative and conventional learning model, the students with high mathematics reasoning skill had mathematics learning achievement as same as those with medium and low mathematics reasoning skill had.